The Elasticity of Taxable Income, Welfare Changes and Optimal Tax Rates - John Creedy (New Zealand Government, The Treasury, 2013)
This paper provides a technical introduction to the use of the elasticity of taxable income in welfare comparisons and optimal tax discussions. It draws together, using a consistent framework and notation, a number of established results concerning marginal welfare changes and optimal taxes. Particular attention is given to the way value judgements can be specified when using this approach, and results are illustrated using the New Zealand income tax. In addition, some new results, particularly in terms of non-marginal tax changes, are presented.
Keywords: H21; H24; H31; 330; Income taxation; Taxable income; Elasticity of taxable income; Excess burden of taxation; Marginal welfare cost; Optimum tax